ANALISIS PENERAPAN E-GOVERNMENT PADA SISTEM INFORMASI MANAJEMEN KEIMIGRASIAN (SIMKIM) DI KANTOR IMIGRASI KELAS 1 KOTA SEMARANG - Rahmawati, Lia Atma; Hariani, Dyah (Journal of Public Policy and Management Review, 2019)
The Immigration Office Class 1 Semarang is one of public service sectors in Indonesia that implement e-government system. The implementation of E-Government at The immigration Office Class 1 Semarang could be seen in the process of making Dokumen Perjalanan Republik Indonesia (DPRI) which is the Republic of Indonesia Travel Document that uses Sistem Informasi Manajemen Kantor Imigrasi or the Immigration Office Management Information System that commonly called SIMKIM. The immigration information system is a unit of various data tabulation and information processes, applications, and also information and communication technology-based devices that are built to unite and connect information systems to all implementers of the integrated Immigration Function. The Immigration function is a part of the state government affairs in providing immigration services, law enforcement, state security, and facilitators of public prosperity development. The purposes of this study are to analyze how e-government is being applied to SIMKIM and what the supporting and inhibiting factors on that system. The method used in this study is qualitative. The results of the research showed that generally the implementation of e-government at SIMKIM Immigration Office Class 1 Semarang has been good. Some obstacles could be overcome with a variety of effective and efficient solutions. The suggestions emphasized by the writer are the improvements of infrastructure, connectivity and human resources.